Pengaruh Work From Home terhadap Work Life Balance dengan Disiplin Kerja sebagai Variabel Intervening pada Masa Pandemi Covid-19 - Calvin Pebrian Zulkarnaen; Francis Hutabarat (IPM2KPE, 2024)
This research aims to understand the effect of working from home on the balance between work and personal life (work-life balance) among workers in Indonesia, by considering work discipline as an intervening variable. This research uses Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the hypothesis, due to the speculative nature of this research. Testing was carried out using SmartPLS 3.0 software. The research results show that working from home does not significantly affect the balance between work and personal life of employees. However, this study found that working from home can improve work discipline, which in turn can contribute to achieving balance between work and personal life. In conclusion, although working from home does not directly result in a balance between work and personal life, efforts to improve work discipline can be an effective strategy in achieving goals. Keywords: Work Discipline, Work From Home, Work Life Balance